The Importance Of Indırect Bondıng In Lıngual Orthodontıcs - Cem Canikoğlu; Yıldız Öztürk (Turkish Journal of Orthodontics, 2004)

(untitled)
Bracket positioning is one of the most important criteria in order to achieve good results in orthodontic treatment and height gauges as currently used in direct bonding, proved to be accurate to solve this problem in labial techniques. However, in lingual orthodontics due to lingual tooth morphology placing the brackets in ideal position becomes very difficult, In this technique treatment results depends on 5 essential parameters which are torque, angulation, height, thichness and rotation. In this study the need of indirect bracket placement related to lingual surface anatomy, interbracket distance and biomechanicall aspect of lingual technique are explained.